ANALISIS NILAI MANFAAT EKONOMI TANAMAN AREN DI DESA KO’MARA KECAMATAN POLONGBANGKENG UTARA KABUPATEN TAKALAR - Muhammad Tahnur; Irma Sribianti; Erlyn Padyla (Jurnal Penelitian Kehutanan BONITA, 2020)
This study aims to determine the value of the economic benefits of sugar palm plants utilized by the community. The research was conducted for 2 months, starting from September to October 2018. The preparatory phase was to determine the location of the study, namely in the Village of Ko'mara, Polongbangkeng District, North Takalar District. With the consideration that in the village there are many sugar palm plants. The next step is identification to see how many people manage palm sugar plants to produce processed palm products. Based on the results of identification obtained 12 respondents. Calculation of the economic value of sugar palm plants is done by calculating income based on market prices. The results showed that sugar palm plants had been processed into Brown Sugar, Kolang Kaling and Ijuk. The value of the economic benefits of the production of Red Sugar is Rp. 99,575,000 / year with a percentage of 69.40%, the production of Kolang-Kaling is Rp. 26,188,000 / year with a percentage of 18.25%, and the production of Ijuk is Rp. 17,700,000 / year with a percentage of 12.33%. The total value of the economic benefits of sugar palm plants is Rp. 143,463,000 / year.